2022
DOI: 10.1183/16000617.0104-2022
|View full text |Cite
|
Sign up to set email alerts
|

Non-Aspergillusmould lung infections

Abstract: Non-Aspergillusfilamentous fungi causing invasive mould infections have increased over the last years due to the widespread use of anti-Aspergillusprophylaxis and increased complexity and survival of immunosuppressed patients. In the few studies that have reported on invasive mould infection epidemiology, Mucorales are the most frequently isolated group, followed by eitherFusariumspp. orScedosporiumspp. The overall incidence is low, but related mortality is exceedingly high. Patients with haematological malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…A study conducted in 23 ICUs across nine European countries identified C. albicans as the predominant Candida species, accounting for approximately 57%, followed by Candida glabrata (21%) and C. parapsilosis (13%) (39). Similarly, previous studies have shown that A. fumigatus is the most common cause of mold infection (92%) (5,40). However, these findings differ from the results of the China Hospital Invasive Fungal Surveillance Net (CHIF-NET).…”
Section: Discussionmentioning
confidence: 88%
“…A study conducted in 23 ICUs across nine European countries identified C. albicans as the predominant Candida species, accounting for approximately 57%, followed by Candida glabrata (21%) and C. parapsilosis (13%) (39). Similarly, previous studies have shown that A. fumigatus is the most common cause of mold infection (92%) (5,40). However, these findings differ from the results of the China Hospital Invasive Fungal Surveillance Net (CHIF-NET).…”
Section: Discussionmentioning
confidence: 88%
“…Scedosporium species are human pathogenic moulds. They are the agents of eumycetoma [1][2][3][4][5], a chronic deep fungal infection of the skin and subcutaneous tissues, and are responsible for a broad spectrum of localised and life-threatening disseminated infections in immunocompetent and immunocompromised individuals [6][7][8][9][10] affecting numerous organs of the body (Figure 1A), including the bones and joints [11][12][13], the central nervous system [14][15][16][17], the eyes [18][19][20][21][22][23][24], the lungs [14,[25][26][27][28][29][30][31][32][33], the sinuses [34][35][36], and other body sites [37][38][39] of cystic fibrosis patients [8,28,[40][41][42], hematopoietic stem-cell and solid organ transplant recipients…”
Section: Introductionmentioning
confidence: 99%
“…Scedosporium species are human pathogenic moulds. They are the agents of eumycetoma [1][2][3][4][5], a chronic deep fungal infection of the skin and subcutaneous tissues, and are responsible for a broad spectrum of localised and life-threatening disseminated infections in immunocompetent and immunocompromised individuals [6][7][8][9][10] affecting numerous organs of the body (Figure 1A), including the bones and joints [11][12][13], the central nervous system [14][15][16][17], the eyes [18][19][20][21][22][23][24], the lungs [14,[25][26][27][28][29][30][31][32][33], the sinuses [34][35][36], and other body sites [37][38][39] of cystic fibrosis patients [8,28,[40][41][42], haematopoietic stem cell and solid organ transplant recipients…”
Section: Introductionmentioning
confidence: 99%